Quality Analysis of PDCA-Based Edupreneurship in 21st-Century Higher Education - Rifaatussalwa Hayati; Diding Nurdin; Eka Prihatin; Cepi Triatna (STAI Hubbulwathan Duri, 2024)
The objective of this qualitative descriptive study is to evaluate the effectiveness of the PDCA (Plan, Do, Check, Act) cycle in enhancing the quality of entrepreneurship education, or